Mitochondrial Dysfunction in Ageing and Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
The past decade has witnessed an explosion of knowledge regarding how mitochondrial dysfunction may translate into ageing and disease phenotypes, as well as how it is modulated by genetic and lifestyle factors. Impairment of the mitochondria may be caused by mutations or deletions in nuclear or mitochondrial DNA. Hallmarks of mitochondrial dysfunction include decreased ATP production, decreased mitochondrial membrane potential, swollen mitochondria, damaged cristae, increased oxidative stress, and decreased mitochondrial DNA copy number. In addition to energy production, mitochondria play an important role in regulating apoptosis, buffering calcium release, retrograde signaling to the nuclear genome, producing reactive oxygen species (ROS), participating in steroid synthesis, signaling to the immune system, as well as controlling the cell cycle and cell growth. Dysfunctional mitochondria have been implicated in ageing and in several diseases, many of which are age-related, including mitochondrial diseases, cancers, metabolic diseases and diabetes, inflammatory conditions, neuropathy, and neurodegenerative diseases such as Alzheimer's, Parkinson's, and Huntington's disease. Additionally, a possible link between mitochondrial metabolism and the ubiquitin-proteasome and autophagy-lysosome systems is emerging as a novel factor contributing to the progression of several human diseases. This special issue calls for original research, mini and full reviews, and perspectives that address the progress and current standing in the vast field of mitochondrial biology. These include, but are not limited to: ageing neurodegenerative diseases mitochondrial diseases metabolic diseases protein homeostasis cell/retrograde signaling oxidative stress pain cancer immune system therapies to counteract mitochondrial dysfunction